Educational Justice: The Cornerstone of Modern Society - Cheng, Xiaoqiao (Science Insights Education Frontiers, 2023)
Educational equity, a key feature of modernized society, is the application of fundamental values of modern culture in education, such as freedom, equality, justice, and human rights (Cole, 2022). It is also a product of education modernization, as well as an essential element of the new era’s education.